George Orwell e a busca pela verdade linguagem, história e memória no universo ficcional de 1984 - LEITE, Paulo Victor Arouche Costa (2018)
This research proposes an investigation of the work of George Orwell 1984, based on in theirs terms Newspeak, Mutability of the Past and Doublethink. These elements enable and guide the exercise of power along of the fictional narrative. We relate each of them to the fundamental dimensions of historiography: language, history and memory, respectively, and a theory of the fictional was also mobilized. For this work, other nonfiction texts of Orwell were fundamental. We seek to situate the process of devaluation of the idea of objective truth and that of the legitimacy of History as an explanatory paradigm of the Western civilization, contextualizing the production of the Orwell's work in terms of the fragmentation process from modernity and the rise of authoritarianism in Europe in the first half of the 20th century